EVALUASI PENERAPAN ASPEK EKOLOGI DALAM PENGELOLAAN HUTAN PRODUKSI LESTARI, PADA PT. PERAWANG SUKSES PERKASA INDUSTRI KABUPATEN KAMPAR RIAU - Albahri Albahri; Aras Mulyadi; Sofyan Husein Siregar (Program Pascasarjana Universitas Riau, 2016)
This study aims to determine how the application of the ecological aspects of the management unit PT. Perawang Sukses Perkasa Industri(PSPI)DistrictLipat Kain that have been certified sustainable plantation management.The research was conductedin Apriland May2014atthe PT. PSPI District Lipat Kain,Kampar, Riau. Application of 6 indicators of ecological aspects by PT. PSPI SFM that have been certified by the Director General of Forestry Enterprises P8 / VI-BPPHH / 2011, general has gone well with the 5 indicators include